(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Handayani R, Dinoto A, Bintang M. 2021. Novel microbial transformation of Andrographis paniculata by Aspergillus oryzae K1A. Biodiversitas 23: 110-117. Microbial transformation is a powerful technique for altering organic substances with complex chemical structures. Aspergillus has been found to produce secondary metabolites from biotransformation products of various medicinal plants. Andrographis paniculata Nees. or sambiloto is an Asian traditional medicinal plant. This study aimed to investigate the microbial transformation of A. paniculata by Aspergillus oryzae K1A. The leaf of A. paniculata was fermented by A. oryzae K1A. Microorganisms were transferred into the ?asks from the slants. The ?asks were placed on rotary shakers, operating at 120 rpm at 37°C. 0.2ml of the substrate solution was added into the fermentation ?asks and these ?asks were maintained under the same conditions and sampling was carried out each day of 0, 1, 3, 7 and 14. The samples were analyzed by TLC, HPLC, and the LC-MS/MS method to evaluate the biotransformation products. The TLC analysis showed different spots of A. paniculata fermented and non-fermented on days of 7 to 14 th and the Rf value was disappeared. The peaks of A. paniculata fermented and non-fermented were relatively similar on days of 0 to 1 incubation and the concentrations of A. paniculata fermented and non-fermented were increased during incubation time in the HPLC analysis. The chromatograms LC-MS/MS study showed different peaks between A. paniculata fermentation and non-fermentation on 3 to 14 days of incubation, and new secondary metabolites picrasidine K (C18H23N3O2); bufotalinin (C24H30O6); and ?-carboline were shown in the table of A. paniculata fermented.